2012
DOI: 10.4236/ojepi.2012.22009
|View full text |Cite
|
Sign up to set email alerts
|

The rise of diabetes prevalence in the Arab region

Abstract: Introduction: Arab populations have many similarities and dissimilarities. They share culture, language and religion but they are also subject to economic, political and social differences. The purpose of this study is to understand the causes of the rising trend of diabetes prevalence in order to suggest efficient actions susceptible to reduce the burden of diabetes in the Arab world. Method: We use principal component analysis to illustrate similarities and differences between Arab countries according to fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Other countries in the "topten" include Kuwait 21.1%, Lebanon 20.2%, Bahrain 19.9%, and United Arab of Emirates 19.2%. [36] Nonetheless, as our data suggests, we think that the proposed prevalence rate of 20% in Saudi Arabia is a low estimate of the real accumulated number of patients with diabetes in the age group 20-79 years. In a study by Alqurashi et al, in 2011, [37] of 6024 participants, diabetes mellitus was present in 1792 patients, i.e., 30% which highly conforms well with our results 34%.…”
Section: Prevalence Of Diabetes Among Respondentsmentioning
confidence: 83%
See 1 more Smart Citation
“…Other countries in the "topten" include Kuwait 21.1%, Lebanon 20.2%, Bahrain 19.9%, and United Arab of Emirates 19.2%. [36] Nonetheless, as our data suggests, we think that the proposed prevalence rate of 20% in Saudi Arabia is a low estimate of the real accumulated number of patients with diabetes in the age group 20-79 years. In a study by Alqurashi et al, in 2011, [37] of 6024 participants, diabetes mellitus was present in 1792 patients, i.e., 30% which highly conforms well with our results 34%.…”
Section: Prevalence Of Diabetes Among Respondentsmentioning
confidence: 83%
“…[2] Furthermore, according to the International Diabetes Federation (IDF), [36] KSA is number 6 of the top ten countries for the prevalence of diabetes and is expected to continue in the coming two decades with the prevalence rate of 20.0% in the age group 20-79 years. This percentage is almost similar to the Saudi MOH report.…”
Section: Prevalence Of Diabetes Among Respondentsmentioning
confidence: 99%
“…Costs associated with complications comprise a large proportion of diabetes-related healthcare budgets when estimated from countries as diverse as Tanzania and the US, Mexico, and South Korea [38][39][40][41] . In the present analysis, while projected treatment costs associated with starting insulin detemir were greater in the studied populations compared with OGLDs, and continued to be throughout the 30-year time horizon, they were partially (Algeria and India) or in essence completely (Indonesia, South Korea, Mexico) offset by the observed reduction in the costs associated with the management of diabetes-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the prevalence of obesity and diabetes in different Arab countries (Table 3). Saudi Arabia has the 5th highest rate of diabetes worldwide, with 20% of the population being affected (47). A study of 17 232 Saudi people in a community-based national epidemiological health survey of the prevalence of obesity reported that nearly 36% of (18), (19), (143) Visfatin Insulin resistance (Not fully explained in humans) (18), (40) Omentin Insulin resistance Enhancement of insulin-stimulated glucose transport (144), (141) Vaspin Insulin resistance (Not fully explained in humans) (18), (141) Retinol-binding protein-4 Insulin resistance Lipid metabolism…”
Section: Adultsmentioning
confidence: 99%